Protein Landscape at Drosophila melanogaster Telomere-Associated Sequence Repeats - Antão, José M. (American Society for Microbiology, 2012)
The specific set of proteins bound at each genomic locus contributes decisively to regulatory processes and to the identity of a cell. Understanding of the function of a particular locus requires the knowledge of what factors interact with that locus and how the protein composition changes in different cell types or during the response to internal and external signals. Proteomic analysis of isolated chromatin segments (PICh) was developed as a tool to target, purify, and identify proteins associated with a defined locus and was shown to allow the purification of human telomeric chromatin. Here we have developed this method to identify proteins that interact with the Drosophila telomere-associated sequence (TAS) repeats. Several of the purified factors were validated as novel TAS-bound proteins by chromatin immunoprecipitation, and the Brahma complex was confirmed as a dominant modifier of telomeric position effect through the use of a genetic test. These results offer information on the efficacy of applying the PICh protocol to loci with sequence more complex than that found at human telomeres and identify proteins that bind to the TAS repeats, which might contribute to TAS biology and chromatin silencing.